Strategies to Leverage Research Funding: Guiding DOD's Peer Reviewed Medical Research Programs - Institute of Medicine (The National Academies Press, 2004)
Since 1992 the Department of Defense (DOD), through the U.S. Army Medical Research and Material Command, has received congressionally earmarked appropriations for programs of biomedical research on prostate, breast, and ovarian cancer; neurofibromatosis; tuberous sclerosis; and other health problems. Appropriations for these Congressionally Directed Medical Research Programs are used to support peer reviewed extramural research project, training, and infrastructure grants.
Keywords: Health and Medicine

Battling Malaria: Strengthening the U.S. Military Malaria Vaccine Program - Institute of Medicine (The National Academies Press, 2006)
Malaria is an infectious disease common to several parts of the world, including Africa, northern South America, and Asia. During their service in the military, U.S. active members may be sent to any part of the world, including parts of the world where Malaria is an issue. In Liberia in 2003, for example, there was a 28 percent attack rate in Marines who spent a short time ashore, and half of the 80 Marines affected needed to be evacuated to Germany. This was not only costly to the U.S. military but dangerous as well. To fight against this disease, there exists a Malaria Vaccine program in the U.S. military. However, there exists a variety of potential vaccine targets for the most severe and important form of malaria; malaria from the species Plasmodium falciparum. Issues also arise with the fact that there are three possible stages to create vaccines against—preerythrocytic, blood, or transmission.
Keywords: Conflict and Security Issues; Health and Medicine

Improving the Social Security Disability Decision Process: Interim Report - Institute of Medicine (The National Academies Press, 2006)
The Institute of Medicine (IOM) Committee on Improving the Disability Decision Process has been working since it first met in January 2005 to develop recommendations to the Social Security Administration (SSA) on how to improve the medical aspects of its disability determination process. By law, Social Security can only pay benefits to those unable to engage in substantial gainful activity because of a "medically determinable physical or mental impairment which can be expected to result in death or which has lasted or can be expected to last for a continuous period of not less than 12 months (emphasis added)." Medical and psychological expertise is critical both in developing the criteria for measuring the severity and functional impact of an impairment or impairments on an applicant's ability to work and in applying the criteria to individual cases where the medical evidence does not clearly meet the criteria in the eyes of a nonmedical disability examiner.
Keywords: Behavioral and Social Sciences

An Assessment of the CDC Anthrax Vaccine Safety and Efficacy Research Program - Institute of Medicine (The National Academies Press, 2003)
In 1998, the Department of Defense (DoD) began a program of mandatory immunization against anthrax for all military personnel. As the program proceeded, however, some military personnel and their families raised concerns about the safety and efficacy of the anthrax vaccine. Acknowledging both the need to protect military personnel and the concerns about the anthrax vaccine, congress directed the Centers for Disease Control and Prevention (CDC) to carry out a research program on its safety and efficacy. To assist in the development of this program, CDC requested the Institute of Medicine (IOM) to convene a committee to review the completeness and appropriateness of the research program. In An Assessment of the CDC Anthrax Vaccine Safety and Efficacy Research Program, the committee makes an overall assessment of the CDD research plan and reviews the specific studies proposed by CDC in the three areas of efficacy, safety and acceptability. The committee also notes additional research needs that became evident following the bioterrorist events of 2001 and makes recommendations about the leadership of the research program.
Keywords: Health and Medicine; Conflict and Security Issues

Protecting Our Forces: Improving Vaccine Acquisition and Availability in the U.S. Military - Institute of Medicine (The National Academies Press, 2002)
Infectious diseases continue to pose a substantial threat to the operational capacity of military forces. Protecting Our Forces reviews the process by which the U.S. military acquires vaccines to protect its warfighters from natural infectious disease threats. The committee found that poorly aligned acquisition processes and an inadequate commitment of financial resources within the Department of Defense vaccine acquisition process – rather than uncleared scientific or technological hurdles – contribute to the unavailability of some vaccines that could protect military personnel and, implicitly, the welfare and security of the nation. Protecting Our Forces outlines ways in which DoD might strengthen its acquisition process and improve vaccine availability. Recommendations, which include combining all DoD vaccine acquisition responsibilities under a single DoD authority, cover four broad aspects of the acquisition process: (1) organization, authority, and responsibility; (2) program and budget; (3)manufacturing; (4) and the regulatory status of special-use vaccines.
Keywords: Health and Medicine; Conflict and Security Issues

The Five Series Study: Mortality of Military Participants in U.S. Nuclear Weapons Tests - Institute of Medicine (The National Academies Press, 2000)
More than 200,000 U.S. military personnel participated in atmospheric nuclear weapons tests between 1945 and the 1963 Limited Nuclear Test Ban Treaty. Questions persist, such as whether that test participation is associated with the timing and causes of death among those individuals. This is the report of a mortality study of the approximately 70,000 soldiers, sailors, and airmen who participated in at least one of five selected U.S. nuclear weapons test series1 in the 1950s and nearly 65,000 comparable nonparticipants, the referents. The investigation described in this report, based on more than 5 million person-years of mortality follow-up, represents one of the largest cohort studies of military veterans ever conducted.
Keywords: Conflict and Security Issues; Health and Medicine

Noise and Military Service: Implications for Hearing Loss and Tinnitus - Institute of Medicine (The National Academies Press, 2006)
The Institute of Medicine carried out a study mandated by Congress and sponsored by the Department of Veterans Affairs to provide an assessment of several issues related to noise-induced hearing loss and tinnitus associated with service in the Armed Forces since World War II. The resulting book, Noise and Military Service: Implications for Hearing Loss and Tinnitus, presents findings on the presence of hazardous noise in military settings, levels of noise exposure necessary to cause hearing loss or tinnitus, risk factors for noise-induced hearing loss and tinnitus, the timing of the effects of noise exposure on hearing, and the adequacy of military hearing conservation programs and audiometric testing. The book stresses the importance of conducting hearing tests (audiograms) at the beginning and end of military service for all military personnel and recommends several steps aimed at improving the military services’ prevention of and surveillance for hearing loss and tinnitus. The book also identifies research needs, emphasizing topics specifically related to military service.
Keywords: Health and Medicine

Advancing Prion Science: Guidance for the National Prion Research Program - Institute of Medicine (The National Academies Press, 2004)
In Advancing Prion Science, the Institute of Medicine’s Committee on Transmissible Spongiform Encephalopathies Assessment of Relevant Science recommends priorities for research and investment to the Department of Defense’s National Prion Research Program (NPRP). Transmissible spongiform encephalopathies (TSEs), also called prion diseases, are invariably fatal neurodegenerative infectious diseases that include bovine spongiform encephalopathy (commonly called mad cow disease), chronic wasting disease, scrapie, and Creutzfeldt-Jakob disease. To develop antemortem diagnostics or therapies for TSEs, the committee concludes that NPRP should invest in basic research specifically to elucidate the structural features of prions, the molecular mechanisms of prion replication, the mechanisms of TSE pathogenesis, and the physiological function of prions’ normal cellular isoform. Advancing Prion Science provides the first comprehensive reference on present knowledge about all aspects of TSEs—from basic science to the U.S. research infrastructure, from diagnostics to surveillance, and from prevention to treatment.
Keywords: Health and Medicine; Agriculture

Advancing Prion Science: Guidance for the National Prion Research Program: Interim Report - Institute of Medicine (The National Academies Press, 2003)
In Advancing Prion Science, the Institute of Medicine's Committee on Transmissible Spongiform Encephalopathies Assessment of Relevant Science recommends priorities for research and investment to the Department of Defense's National Prion Research Program (NPRP). Transmissible spongiform encephalopathies (TSEs), also called prion diseases, are invariably fatal neurodegenerative infectious diseases that include bovine spongiform encephalopathy (commonly called mad cow disease), chronic wasting disease, scrapie, and Creutzfeldt-Jakob disease. To develop antemortem diagnostics or therapies for TSEs, the committee concludes that NPRP should invest in basic research specifically to elucidate the structural features of prions, the molecular mechanisms of prion replication, the mechanisms of TSE pathogenesis, and the physiological function of prions' normal cellular isoform. Advancing Prion Science provides the first comprehensive reference on present knowledge about all aspects of TSEs' from basic science to the U.S. research infrastructure, from diagnostics to surveillance, and from prevention to treatment. This report summarizes the progress thus far.
Keywords: Health and Medicine

Interactions of Drugs, Biologics, and Chemicals in U.S. Military Forces - Institute of Medicine (The National Academies Press, 1996)
Keywords: Health and Medicine; Conflict and Security Issues

Giving Full Measure to Countermeasures: Addressing Problems in the DoD Program to Develop Medical Countermeasures Against Biological Warfare Agents - Institute of Medicine; National Research Council (The National Academies Press, 2004)
In recent years, substantial efforts have been initiated to develop new drugs, vaccines, and other medical interventions against biological agents that could be used in bioterrorist attacks against civilian populations. According to a new congressionally mandated report from the Institute of Medicine and National Research Council of the National Academies, to successfully develop these drugs, vaccines, and other medical interventions against biowarfare agents, Congress should authorize the creation of a new agency within the Office of the Secretary of the U.S. Department of Defense. The committee recommended that Congress should improve liability protections for those who develop and manufacture these products, to stimulate willingness to invest in new research and development for biowarfare protection. Giving Full Measure to Countermeasures also identifies other challenges—such as the need for appropriate animal models and laboratories equipped with high-level biosafety protections—that will require attention if DoD efforts to develop new medical countermeasures are to be successful.
Keywords: Conflict and Security Issues; Health and Medicine

Accelerating the Research, Development, and Acquisition of Medical Countermeasures Against Biological Warfare Agents: Interim Report - Institute of Medicine; National Research Council (The National Academies Press, 2003)
Keywords: Conflict and Security Issues

Long-Term Health Effects of Participation in Project SHAD (Shipboard Hazard and Defense) - Institute of Medicine (The National Academies Press, 2007)
More than 5,800 military personnel, mostly Navy personnel and Marines, participated in a series of tests of U.S. warship vulnerability to biological and chemical warfare agents, Project SHAD (Shipboard Hazard and Defense), in the period 1962-1973. Only some of the involved military personnel were aware of these tests at the time. Many of these tests used simulants, substances with the physical properties of a chemical or biological warfare agent, thought at the time to have been harmless. The existence of these tests did not come to light until many decades later. In September 2002, the Institute of Medicine (IOM) agreed to undertake a scientific study, funded by the Veterans' Affairs, of potential long-term health effects of participation in Project SHAD. In general, there was no difference in all-cause mortality between Project SHAD participants and nonparticipant controls, although participants statistically had a significantly higher risk of death due to heart disease, had higher levels of neurodegenerative medical conditions and higher rates of symptoms with no medical basis. Long-Term Health Effects of Participation in Project SHAD focuses on the potential health effects of participation in Project SHAD. It is a useful resource for government defense agencies, scientists and health professionals.
Keywords: Health and Medicine; Environment and Environmental Studies